Aplication of techno-marketing programme package of Indonesian orthodox black tea to analyze the Russian Federation market - Suprihatini, Rohayati (Research Institute for Tea and Cinchona, 2013)
In order to increase market share as well as competitiveness of Indonesian orthodox black tea in Russian Federation as the biggest Indonesian tea export destination, a research to analyze Russian Federation market applying tea techno-marketing programme package especially to finding suggestions in improving process production has been conducted. This programme consist of Data Base Management System, Knowledge Base Management System, Model Base Management System, and Dialogue Management System. Four data analysis techniques were applied namely (1) market trend, (2) comparative performa index (CPI), (3) constant market share (CMS), and (4) quality function deployment (QFD). The results showed that the Russian Federation market prefer the medium grown tea which is dominated by broken grade (91%). Minimum sensory test score for appearance of made tea, taste, aroma, and colour of liquor as well as infused leaf to be accepted in Russian Federation market were medium. To comply with a request of Russian Federation market, main production process aspects had to be improved, were the quality of tea shoots, had to be 65% minimum, and the rolling programme in factory to result in 90% of broken grades.